1999
DOI: 10.1002/hep.510300138
|View full text |Cite
|
Sign up to set email alerts
|

Liver and bile duct pathology followingCryptosporidium parvum infection of immunodeficient mice

Abstract: Cryptosporidium parvum (CP) is an apicomplexan parasite that causes trivial diarrhea in healthy subjects 1 and lifethreatening hepatobiliary, gastrointestinal, or respiratory tract infection in subjects with acquired immune deficiency syndrome 2-4 or CD154 deficiency (which causes X-linked immunodeficiency with hyper IgM [XHIM]). 5 The parasite is difficult to culture, and experimental studies have mostly used immunodeficient mice, particularly those with severe combined immunodeficiency (SCID), as models. 6-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…However, the presence of portal fibrosis, biliary sclerosis, and necrosis with dilation of ductlike structures lined by highly atypical biliary epithelial cells was found in IFN-γ knockout mice infected with Cryptosporidium . 25 These changes, classified as low-grade dysplasia, 25 are consistent with our results. Interestingly, similar histologic findings (especially Figure 3 in Mead and others 23 ) were associated with chronic C. parvum infection in NIH-III nu/nu mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the presence of portal fibrosis, biliary sclerosis, and necrosis with dilation of ductlike structures lined by highly atypical biliary epithelial cells was found in IFN-γ knockout mice infected with Cryptosporidium . 25 These changes, classified as low-grade dysplasia, 25 are consistent with our results. Interestingly, similar histologic findings (especially Figure 3 in Mead and others 23 ) were associated with chronic C. parvum infection in NIH-III nu/nu mice.…”
Section: Discussionsupporting
confidence: 91%
“…24 Others authors have reported that liver involvement occurs later, in some cases 13-26 weeks PI. 25 However, we found that C. parvum parasites under Dex develop predominantly in the ileocaecal region and in the colon of SCID mice (Reference 6 and present work) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 44%
“…In this study, liver section from five mice of group (IIa) showed inflammatory changes with no fibrosis, 30 days post-infection. Stephens et al [29] reported that chronic infections of the biliary tract with C. parvum in SCID mice developed triaditis, cholangitis and lobular hepatitis. Moreover dysplastic changes in the liver after C. parvum infection have been reported in SCID mice [30].…”
Section: Discussionmentioning
confidence: 99%
“…18 There is also evidence that CD40-CD40L interactions between T cells and biliary epithelial cells infected with C parvum may be important in triggering apoptosis of infected cells and thereby promoting clearance of infection. 19 This immune defense would be restored in X-HIM patients after successful HSCT. Therefore, the favorable hepatic outcome that we observed in our patients after HSCT may reflect reconstitution of host defense with clearance of an underlying infectious process.…”
Section: Discussionmentioning
confidence: 99%